Pengembangan Model Rantai Pasok Bahan Baku Untuk Meningkatkan Produktivitas Produksi Jamu Bubuk Pada Toko Online Griya Nature - Hafiz Ilham Ardana; Akbar Izdihar; Daud Arya Rafa; Seftin Fitri Ana Wati (Universitas Pahlawan Tuanku Tambusai, 2024)
This study aims to understand and enhance the productivity of the medicinal spice supply chain at Griya Nature Online Store through a dynamic systems approach. Medicinal spices are a prominent commodity of Indonesia with significant potential in international markets, as well as the pharmaceutical and traditional beverage industries. This research analyzes factors affecting the supply chain's productivity, both internal (consumer demand, herbal medicine sales, store profits) and external (urban expansion, land clearing, climate, production disruptions). The research methodology includes data collection through interviews and analysis of relevant variables. A causal model was developed using Causal Loop Diagrams (CLD) and mathematical models with Stock and Flow diagrams simulated using Vensim software. Simulation results indicate that productivity improvement can be achieved through optimal management of these factors. Model verification and validation ensure accurate representation of the real system, allowing the model to be used to simulate policy scenarios aimed at increasing the effectiveness and efficiency of supply chain management. This study provides valuable insights for industries and SMEs involved in the production and marketing of medicinal spices. Through the dynamic systems approach, supply chain obstacles can be identified and addressed, improving productivity and product distribution optimization. The results of this research are expected to make a significant contribution to the development of the medicinal spice industry in Indonesia.